Wznowienie postępowania w polskim prawie procesowym cywilnym w latach 1933–1939 - Krygier, Grzegorz (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The validity of court rulings was extremely important to the judiciary. It served to uphold the authority of court rulings, the legal order and the interests of the state. However, when a ruling turned out to be obviously wrong and unjust, there had to be a possibility for the proceedings to be resumed and end with a valid ruling. In 1918–1933 the binding civil procedure in Poland was that of the partitioning powers. The German, Austrian and Russian procedures provided for a possibility of proceedings to be resumed, but resolved the issue in a variety of ways. The members of the Codification Commission faced the difficult task of creating a uniform instrument of resumptionof proceedings. The author of the present article discusses the problems facing both the authors of the 1930 Code of Civil Procedure as well as people who subsequently applied the provisions of the code in practice.
Keywords: nieważność postępowania sądowego; orzeczenia sądowe; postępowanie cywilne; wznowienie postępowania; żądanie wznowienia postępowania